Action of Neurotransmitter: A Key to Unlock the AgRP Neuron Feeding Circuit - Liu, Tiemin; Wang, Qian; Berglund, Eric D.; Tong, Qingchun (Frontiers in Neuroscience, 2013)
The current obesity epidemic and lack of efficient therapeutics demand a clear understanding of the mechanism underlying body weight regulation. Despite intensive research focus on obesity pathogenesis, an effective therapeutic strategy to treat and cure obesity is still lacking. Exciting studies in last decades have established the importance of hypothalamic agouti-related protein-expressing neurons (AgRP neurons) in the regulation of body weight homeostasis. AgRP neurons are both required and sufficient for feeding regulation. The activity of AgRP neurons is intricately regulated by nutritional hormones as well as synaptic inputs from upstream neurons. Changes in AgRP neuron activity lead to alterations in the release of mediators, including neuropeptides NPY and AgRP, and fast-acting neurotransmitter GABA. Recent studies based on mouse genetics, novel optogenetics and designer receptor exclusively activated by designer drugs (DREADD) have identified a critical role for GABA release from AgRP neurons in the parabrachial nucleus and paraventricular hypothalamus in feeding control. This review will summarize recent findings about AgRP neuron-mediated control of feeding circuits with a focus on the role of neurotransmitters. Given the limited knowledge on feeding regulation, understanding the action of neurotransmitters may be a key to unlock neurocircuitry that governs feeding.